2008
DOI: 10.1111/j.1365-2982.2008.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of κ‐opioid receptors in visceral nociception in mice

Abstract: It has been shown that the behavioural responses to chemically evoked visceral nociception are increased in transgenic mice lacking the j-opioid receptor (KOR). The aim of the present study was to evaluate the contribution of KOR in mechanically evoked visceral pain by performing colorectal distension (CRD) and monitoring the subsequent visceromotor response (VMR) in control mice (KOR +/+ ) and in mice lacking KOR (KOR )/) ). Pseudo-affective visceral pain responses were evoked in conscious mice using increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(78 reference statements)
0
7
0
1
Order By: Relevance
“…Here, we have shown an increase in visceromotor response to CRD in naïve MOR and DOR global KO mice, indicating that global activity at these two opioid receptors regulates basal visceral pain. A previous study has found a normal sensitivity to CRD in kappa opioid receptor KO mice (Larsson et al., ), and altogether this suggests that global MOR and DOR activities have major influences on the response to colon distension. In assays of visceral chemical nociception to intraperitoneal acetic acid, MOR KO mice showed diminished or normal writhing response (Sora et al., ; Weibel et al., ), DOR KO showed no phenotype (Filliol et al., ) and KOR KO mutants were more sensitive than wild‐type mice (Simonin et al., ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Here, we have shown an increase in visceromotor response to CRD in naïve MOR and DOR global KO mice, indicating that global activity at these two opioid receptors regulates basal visceral pain. A previous study has found a normal sensitivity to CRD in kappa opioid receptor KO mice (Larsson et al., ), and altogether this suggests that global MOR and DOR activities have major influences on the response to colon distension. In assays of visceral chemical nociception to intraperitoneal acetic acid, MOR KO mice showed diminished or normal writhing response (Sora et al., ; Weibel et al., ), DOR KO showed no phenotype (Filliol et al., ) and KOR KO mutants were more sensitive than wild‐type mice (Simonin et al., ).…”
Section: Discussionmentioning
confidence: 71%
“…Colitis models induced by either 2,4,6‐trinitrobenzene sulphonic acid (TNBS), adoptive transfer of CD4 + CD45RB high T lymphocytes or dextran sodium sulphate (DSS) have shown that endogenous mu opioid activity dampened inflammation (Philippe et al., ; Goldsmith et al., ; Sobczak et al., ; Anselmi et al., ), and the expression of MOR (Pol et al., ) and DOR (Pol et al., ) was increased during intestinal inflammation in mice. Although KOR activation produced visceral anti‐hyperalgesia (Sengupta et al., ; Sobczak et al., ; Mosinska et al., ), a comparable sensitivity to CRD was found in KOR knockout (KO) and wild‐type (WT) mice (Larsson et al., ) suggesting no major implication of the endogenous KOR tone. However, the contribution of endogenous MOR and DOR activities on visceromotor responses to colorectal distension (CRD) under basal (naïve) and acute inflammatory conditions is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…42 ) and/or low affinity for the -opioid receptor (e.g., Allescher et al 43 ). These clinical reports, together with physiologic evidence for a role of -opioid receptors in modulating visceral pain, 44,45 have lead to an intensified search for high-affinity, peripherally selective -opioids.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that fentanyl significantly reduces visceromotor responses to a greater extent when kappa receptors are nonfunctional (kappa receptor gene “knocked-out” mice) [148]. The combination of fentanyl and the kappa receptor agonist spiradoline produced dose-dependent supra-additive antinociception in an animal model involving colorectal distention.…”
Section: Important Channels Receptors and Mediators Of Visceral mentioning
confidence: 99%